Inequalities in the distribution of COVID‐19‐related financial difficulties for Australian families with young children. (13th April 2022) - O'Connor, Meredith; Greenwood, Christopher J.; Letcher, Primrose; Giallo, Rebecca; Priest, Naomi; Goldfeld, Sharon; Hope, Steven; Edwards, Ben; Olsson, Craig A.
Abstract: Background: We examine (1) the frequency of financial difficulties in Australian families with young children (0–8 years) in the early and later phases of the pandemic; (2) the extent to which parents' pre‐pandemic socio‐economic disadvantage (SED) predicted financial difficulties; and (3) whether grandparent intergenerational SED further amplified this risk. Method: Data : Australian Temperament Project (ATP; established 1983, N  = 2443) and ATP Generation 3 study (ATPG3; established 2012; N  = 702), of which 74% ( N  = 553) completed a COVID‐specific module in the early (May–September 2020) and/or later (October–December 2021) phases of the pandemic. Outcomes : Parent‐reported loss of employment/reduced income, difficulty paying for essentials, and financial strain. Exposures : Pre‐pandemic parent and grandparent education and occupation. Analysis : Logistic regressions, estimated via generalized estimating equations, were used to examine associations between the pre‐pandemic SED of parents and grandparents and their interaction with financial difficulties, adjusting for potential confounders. Results: At both pandemic time points, a third of parents reported adverse financial impacts (early: 34%, 95% confidence interval [CI] = 30–38; later: 32%, 95% CI = 28–36). Each standard deviation increase in the parents' pre‐pandemic SED was associated with a 36% increase in the odds of reporting multiple financial difficulties (odds ratio [OR] = 1.36, 95% CI = 1.04–1.78). There was little evidence of an interaction between the SED of parents and grandparents. Conclusions: Financial impacts related to the COVID‐19 pandemic were common and, irrespective of grandparent SED, disproportionately borne by parents with higher pre‐pandemic SED. Given the well‐established relationship between disadvantage and child health and development, sustained and well‐targeted government supports will be critical to minimizing adverse impacts in years to come.